Comparison of Paraquat Herbicide Removal from Aqueous Solutions using Nanoscale Zero-Valent Iron-Pumice/Diatomite Composites - Abbas Khodabakhshi; Fazel Mohammadi-Moghadam; Mohammad Mehdi Amin; Sara Hamati; Shakila Hayarian (International Journal of Chemical Engineering)
Paraquat is the most important herbicide of the bipyridyl group. The aim of the present study was to compare the removal of paraquat herbicide from aqueous solutions using nanoscale zero-valent iron-pumice/diatomite composites. In this study, nZVI was supported with diatomite and pumice. Scanning electron microscopy (SEM) analysis, X-ray diffraction spectroscopy (XRD), Fourier transform infrared spectrometry (FTIR), and specific surface area tests (BET) were used to evaluate the properties of nanoadsorbents. The residual concentration of paraquat in aqueous solution was detected by high-performance liquid chromatography (HPLC). Then, the effects of different variables including the pollutant concentration, contact time, temperature, adsorbents (D-nZVI and P-nZVI) dose, and pH, were investigated in a lab scale batch system. The results showed that the optimal pH for both processes was 3.74. In optimal conditions, the efficiencies of D-nZVI and P-nZVI were 92.76% and 85.28%, respectively. In addition, isotherm and adsorption kinetics studies indicated that P-nZVI follows the Langmuir and Freundlich isotherm models, and D-nZVI follows the Langmuir isotherm model, and both processes follow pseudo-second-order kinetics. The results indicated that the synthesized nanoparticles were suitable for removing paraquat from aqueous solutions. Both adsorbents were found to be very effective in removing similar compounds at ambient temperature in a short time.